MODERN EDUCATIONAL TRENDS IN THE TRAINING OF SPECIALISTS IN ONCOLOGY IN RUSSIAN FEDERATION - M. I. Davydov; Sh. Kh. Gantsev; L. Z. Velsher; I. V. Poddubnaya; V. N. Pavlov; L. V. Demidov; V. G. Polyakov; I. S. Stilidi; I. R. Rakhmatullina; A. M. Khanov (Креативная хирургия и онкология, 2017)
The  article  summarizes  the   experience  of  academic  and   pedagogical  leading   of universities  in Russia  to  train  specialists  of  new  formation in oncology, in accordance with the challenges of modern society and the needs  of the modernized health. There are prospects and  the  possibility of  the  introduction of  advanced educational technology in health professional education on the basis of the competence approach. The modern model of  continuing professional development is implemented in the  departments of  oncology leading Russian universities.